Belajar Matematika Menggunakan Strategi yang Menyenangkan untuk Siswa SD - Tul Mawaddah, Anisa; Safitri, Adek (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
Steps to overcome disparities in preparation for studying abstract mathematics require the use of modern technology and media such as educational games and mathematical applications, mathematical games. Therefore, an educator creates mathematical game activities that involve the main material being studied and concentrate on following the level of intelligence of students according to John Peaget in Fremon, 1969) stating that children at elementary and middle school age are still in the concrete operational phase, The approach will be adjusted in mathematics lessons, efforts are made to understand abstract concepts in mathematics, abstractions can be transformed into real objects.Adapting to children's basic needs for playing, they will enjoy learning in a special way, this game is presented in children's hearts, there will be happiness to master mathematics.